2022
DOI: 10.48550/arxiv.2202.06184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breakdown of bulk-projected isotropy in surface electronic states of topological Kondo insulator SmB$_6$(001)

Abstract: The topology and spin-orbital polarization of two-dimensional (2D) surface electronic states have been extensively studied in this decade. One major interest in them is their close relationship with the parities of the bulk (3D) electronic states. In this context, the surface is often regarded as a simple truncation of the bulk crystal. Here we show breakdown of the bulk-related in-plane rotation symmetry in the topological surface states of the Kondo insulator SmB 6 . Angle-resolved photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As an alternative solution to avoid the multi-domain problem, we have just tried to apply a small miscut angle on the (001) surface. Although the whole discussion of this sample is still under review, the surface bands themselves were observed clearly there [63].…”
Section: Smb 6 (001)mentioning
confidence: 96%
“…As an alternative solution to avoid the multi-domain problem, we have just tried to apply a small miscut angle on the (001) surface. Although the whole discussion of this sample is still under review, the surface bands themselves were observed clearly there [63].…”
Section: Smb 6 (001)mentioning
confidence: 96%